Enhancement of folk story writing containing pancasila profile character values - Sintowati Rini Utami; Siti Ansoriyah; Nur Sekhudin (University of Muhammadiyah Malang, 2025)
The aim of this research is to develop the writing of folk tales that contain the character values of the Pancasila profiles as reading material recounts. The character values in folklore are developed based on themes and messages, encompassing global diversity, mutual cooperation, creativity, critical thinking, independence, and faith in God Almighty. Understanding these values is reinforced through folklore retelling. The folklore development follows the ADDIE model with three main stages: analysis, design, and development. Data were collected from orally transmitted folklore, including fables, myths or legends, adventure stories, fantasy tales, and fairy tales. Analysis was conducted on folklore structure, retold story structure, Pancasila character values, and the need for folklore writing through surveys and expert validation. The folklore development stage involved validation by teachers, education experts, and students. Data analysis was conducted using a qualitative descriptive approach. The quality of folklore teaching materials received an excellent rating, with scores of 95% from textbook subject matter expert and 93% from storyteller experts. Thus, folklore containing Pancasila character values is deemed suitable for implementation in the MK lecture on the development of teaching materials in language. Indonesian Language and Literature Education Study Program and study materials for the MK Literacy in the Language Education Masters Study Program